The Role of Section 2 of the Sherman Act in International Patent Fraud: “Walk Softly and Carry a Big Stick” - David E. Steinberg (Washington University Law Quarterly, 1981)
This Article analyzes the monopolistic implications of Mannington Mills and considers the point at which international patent fraud may be determined unlawful monopolization or an unlawful attempt to monopolize.
Keywords: Antitrust law; Patent law; Sherman Act; United States